Infanticide and cannibalism of juvenile polar bears (Ursus maritimus) in Svalbard ... - Wiig, O.; Derocher, A.E. (University of Alberta Library, 1999)
Two instances of infanticide and cannibalism in polar bears (Ursus maritimus) were observed in SE Svalbard, at Hopen Island. In the first, an adult male killed three young cubs at a den site and consumed one of them. In the second, an adult male actively pursued, killed, and consumed a dependent yearling. Infanticide of dependent polar bear offspring by adult males may be more common in Svalbard than in other populations because the population is close to carrying capacity or because geographic features reduce spatial segregation of age and sex classes. ...